Konsep Akhlak dalam Perspektif Hadis Nabi Menggunakan Metode Tematik - Nurul Mawahda Iskandar; Susanti Vera; Agus Suyadi Raharusun (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study is to discuss the concept of morality according to the hadith of the Prophet. This research method uses a qualitative type through literature study and content analysis. The results and discussion of this research include general views on morality, traditions about morality, and the concept of morality in the Prophet's hadith. This study concludes that Islam highly upholds morality (akhlaqul karimah), this is confirmed in the Qur'an, and also that morality is the mission of the Messenger of Allah to perfect the morals of mankind, so that morality becomes a reflection when interacting with Allah and with other creatures. Based on the hadith of the Prophet, it is explained that the most perfect believer is the one with the best morals. This research is expected to have benefits for enriching the treasures of Islamic knowledge.